Molecular determinants of origin discrimination by Orc1 initiators in archaea. - Dueber, E; Costa, A; Corn, J; Bell, S; Berger, J (Oxford University Press, 2011)
Unlike bacteria, many eukaryotes initiate DNA replication from genomic sites that lack apparent sequence conservation. These loci are identified and bound by the origin recognition complex (ORC), and subsequently activated by a cascade of events that includes recruitment of an additional factor, Cdc6. Archaeal organisms generally possess one or more Orc1/Cdc6 homologs, belonging to the Initiator clade of ATPases associated with various cellular activities (AAA(+)) superfamily; however, these proteins recognize specific sequences within replication origins. Atomic resolution studies have shown that archaeal Orc1 proteins contact double-stranded DNA through an N-terminal AAA(+) domain and a C-terminal winged-helix domain (WHD), but use remarkably few base-specific contacts. To investigate the biochemical effects of these associations, we mutated the DNA-interacting elements of the Orc1-1 and Orc1-3 paralogs from the archaeon Sulfolobus solfataricus, and tested their effect on origin binding and deformation. We find that the AAA(+) domain has an unpredicted role in controlling the sequence selectivity of DNA binding, despite an absence of base-specific contacts to this region. Our results show that both the WHD and ATPase region influence origin recognition by Orc1/Cdc6, and suggest that not only DNA sequence, but also local DNA structure help define archaeal initiator binding sites.